Serological evidence of Rift Valley fever infection and risk factors among one-humped camels (Camelus dromedarius) in Northern Nigeria - Musa, Adamu Andrew; Ayo, Yila Simon; Lushakyaa3, Allam (https://doi.org/10.1101/2020.01.10.901470, 2020)
Background: Rift Valley fever (RVF) is a zoonotic disease that has become emerging and reemerging in some regions of the world, infecting livestock and humans. One-humped camels are important economic livestock species in Africa used for traction, transportation, and food. Regional and international trade has continued to increase the risk of this disease, spreading widely and causing severe economic and public health catastrophes in affected regions. In spite of these risks, there is a dearth of information about the status of RVF in camels in Nigeria. This study was carried out to determine the prevalence of the RVF virus in one-humped camels in Nigeria and identify the risk factors associated with the disease. Methods: A cross-sectional study with simple random sampling was carried out in seven local government areas of Jigawa and Katsina States. The sera from camels were tested for anti-RVFV IgG. Camel owners were administered a structured questionnaire to ascertain their knowledge, attitude, and practice. Results: An overall prevalence of 19.9% (95% CI; 17.07-22.90) was recorded. Based on age groups, the highest prevalence of 20.9% (95% CI; 17.00-25.31) was obtained among older camels (6-10 years), while female camels recorded a high prevalence of 20.4% (95%CI; 15.71- 25.80). Sule Tankar-kar recorded the highest prevalence with 33% (95%CI; 1.31-4.72, p= 0.007) and OR 2.47 in Jigawa State while Mai’adua had 24.7% (95%CI; 0.97-2.73, p=0.030) with OR 1.62 in Katsina State respectively. From the risk map, local government areas bordering Niger Republic were at a high risk of RVF. Only high rainfall was not significantly linked with RVF occurrence among nomadic camel pastoralists (95%CI 0.93-5.20; p=0.070). Conclusion: There is a need for the country to have quarantine units across borders for screening animals coming from neighbouring countries for transboundary infectious diseases such as RVF
Keywords: Rift Valley Fever (RVF); Nigeria; Camels; Zoonosis; Ahmadu Bello University; ACENTDFB; Sackey Anthony; Alhaji Nma Bida; Garba Bello Sikiti